1991
DOI: 10.21273/hortsci.26.9.1178
|View full text |Cite
|
Sign up to set email alerts
|

Strawberry Growth and Photosynthetic Responses to Paclobutrazol

Abstract: Foliar sprays of increasing concentrations (0, 75, 150, 300, 600, and 1200 mg·liter-1) of paclobutrazol were applied to `Cardinal' strawberry plants (Fragaria × ananassa Duch.) 35 days after transplanting. The plants were established in August in cultivated plots for measurement of paclobutrazol effects on first year growth or in a double-row hill system on black polyethylene-covered raised beds for 2nd year measurements. Increasing the paclobutrazol conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
2

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 3 publications
0
15
0
2
Order By: Relevance
“…While forsythia did not exhibit an increase in P N before 55 DAT, other researchers have demonstrated triazole-induced increases in P N for 'Cardinal' strawberry (Fragaria ×ananassa Duch.) within 12 DAT (Deyton et al, 1991). However, both strawberry (Deyton et al, 1991) and forsythia had higher levels of P N when measured on the new leaves produced the following growing season.…”
Section: Result's and Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…While forsythia did not exhibit an increase in P N before 55 DAT, other researchers have demonstrated triazole-induced increases in P N for 'Cardinal' strawberry (Fragaria ×ananassa Duch.) within 12 DAT (Deyton et al, 1991). However, both strawberry (Deyton et al, 1991) and forsythia had higher levels of P N when measured on the new leaves produced the following growing season.…”
Section: Result's and Discussionmentioning
confidence: 91%
“…within 12 DAT (Deyton et al, 1991). However, both strawberry (Deyton et al, 1991) and forsythia had higher levels of P N when measured on the new leaves produced the following growing season. Increased chlorophyll concentration and decreased ratio of Chl a and Chl b resulting from uniconazole application may influence CO 2 exchange and assimilation and may contribute to the P N increase reported herein.…”
Section: Result's and Discussionmentioning
confidence: 91%
“…AMO-1618 increased flower induction in SD cultivars grown under noninductive long days (Avigdori-Avidov et al 1977). This was attributed to a source-sink effect, either by promoting photosynthesis, thereby increasing assimilate availability (Deyton et al 1991) or by decreasing vegetative growth, resulting in increased assimilate partitioning to reproductive growth (Bish et aI., 1996). This was attributed to a source-sink effect, either by promoting photosynthesis, thereby increasing assimilate availability (Deyton et al 1991) or by decreasing vegetative growth, resulting in increased assimilate partitioning to reproductive growth (Bish et aI., 1996).…”
Section: Identification Of the Floral Promoter/inhibitormentioning
confidence: 99%
“…Published studies have indicated that runnering can be increased with applications of gibberellins (GA) (Kender et al, 1971;Tehranifar and Battey, 1997), cytokinins (Biain de Elizalde and Guitman, 1979;Hasse et al, 1989;Pritts et al, 1986;Waithaka and Dana, 1978) or combinations of these (Kender et al, 1971;Waithaka and Dana, 1978). As a result, a wide range of growth inhibitors targeting GA biosynthesis or response have been tested for suppression of runners (Archbold 1986(Archbold , 1989Bish et al, 1996;Deyton et al, 1991;Hasse et al, 1989;Ibrahim and Mohamed, 1993;McArthur and Eaton, 1987). Of these, the most consistently effective has been the strong biosynthesis inhibitor paclobutrazol (Archbold, 1989;Bish et al, 1996;Deyton et al, 1991).…”
mentioning
confidence: 99%